Critical Success Factors For Malaysian Contractors In International Construction Projects - Singh, Amarpreet Kaur Mahinder (Universiti Sains Malaysia, 2019)
Currently, the construction projects are advancing gradually around the world as a result of the recent global economic crisis. In order to accommodate public needs within the current economic situation, the Malaysian Government has confined the acquirement of public sector projects to “necessary to meet public need” extends just subsequently narrowing the quantity of domestic projects accessible. A tremendous demand of development worldwide has picked up enthusiasm of Malaysian construction firms to go into international construction projects. Therefore, most major contractors have decided to change their focus by looking into international projects outside Malaysia not exclusively to guarantee the suitability of their businesses but also for long-term survival. Even though, some Malaysian contractors have managed to penetrate successfully into international construction projects, their critical success factors (CSFs) are absolutely obscure. Thus, the aim of this study is to determine the Critical Success Factors (CSFs) of Malaysian Contractors in International construction projects. A general literature review and initial interview was completed and results show on the CSFs of Malaysian contractors in International construction projects. This study is based on interviews with project managers, and the person in charged with CIDB International department. They have established an excellent reputation and worldwide success in the last decade. The CSFs are then exhibited in the form of AHP priority-ranking model, which prioritizes the success factors distinguished in successive way, from the most up to the less critical ones. The establishment of this kind of priority-ranking model enables contractors in Malaysia to not just recognize the key components or factors that should be completely considered and managed yet in addition enable them to get ready appropriate mitigation strategies and contingency plans prior to entering into international construction projects.